(untitled) (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: World health develops by huge progressive tempos. Each separate state has features of health-care system. Despite this, there are only few general models of health care all over the world. Scientific summarizing of main legal and organizational and economic aspects of functioning of each of general models of health care system should has a place periodically including its topical changes. This is the purpose of our review. Materials and Methods: We used empirical methods (data collection, study, and comparison), methods of comparative analysis, and generalization of statistical data. It has been used regulatory legal acts regulating the functioning of health systems, reports from the World Health Organization (WHO), Bloomberg analytical agency, and Foundation for Public Welfare (published in English on the site) also. Results and Discussion: Shot comparative characteristic of the functioning of the main models of health-care systems and analysis of the indexes of the efficiency of functioning of the health-care models including all available disadvantages allows us to conclude about slightly higher efficiency of the one model compared to others (the state system and the Beveridge system). Conclusion: Assessment of the approaches for describing the effectiveness of the functioning of health-care systems allows us to describe two mechanisms of calculation of the health-care effectiveness index - the Bloomberg and The Commonwealth Fund. The obtained results allow claiming that the most effective model of health-care system is system of public health financing. Given study shows the features and predicted benefits of actual models of health-care systems. Given results may be used in the process of reforming of health-care system for the developing and developed countries.